Dissecting the role of non-coding RNAs in the accumulation of amyloid and tau neuropathologies in Alzheimer’s disease - Patrick, Ellis; Rajagopal, Sathyapriya; Wong, Hon-Kit Andus; McCabe, Cristin; Xu, Jishu; Tang, Anna; Imboywa, Selina H.; Schneider, Julie A.; Pochet, Nathalie; Krichevsky, Anna M.; Chibnik, Lori B.; Bennett, David A.; et al. (Molecular neurodegeneration, 2017)
Given multiple studies of brain microRNA (miRNA) in relation to Alzheimer's disease (AD) with few consistent results and the heterogeneity of this disease, the objective of this study was to explore their mechanism by evaluating their relation to different elements of Alzheimer's disease pathology, confounding factors and mRNA expression data from the same subjects in the same brain region. We report analyses of expression profiling of miRNA (n = 700 subjects) and lincRNA (n = 540 subjects) from the dorsolateral prefrontal cortex of individuals participating in two longitudinal cohort studies of aging. We confirm the association of two well-established miRNA (miR-132, miR-129) with pathologic AD in our dataset and then further characterize this association in terms of its component neuritic β-amyloid plaques and neurofibrillary tangle pathologies. Additionally, we identify one new miRNA (miR-99) and four lincRNA that are associated with these traits. Many other previously reported associations of microRNA with AD are associated with the confounders quantified in our longitudinal cohort. Finally, by performing analyses integrating both miRNA and RNA sequence data from the same individuals (525 samples), we characterize the impact of AD associated miRNA on human brain expression: we show that the effects of miR-132 and miR-129-5b converge on certain genes such as EP300 and find a role for miR200 and its target genes in AD using an integrated miRNA/mRNA analysis. Overall, miRNAs play a modest role in human AD, but we observe robust evidence that a small number of miRNAs are responsible for specific alterations in the cortical transcriptome that are associated with AD.